Pengendalian Jamur Ganoderma dengan Metode Perbanyakan Jamur Trichoderma pada Pembibitan Kelapa Sawit di PT PP London Sumatra Bah Lias Research Station - Utami, Mutiara Alya; Nasution, Rizki Amelia; Mawaddah, Fitri Asyiatun; Aulia, Rahma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Ganoderma sp. usually attack from the root or base of the trunk on the tree whether the tree is alive or dead. There are also other species of Ganoderma whose pileus attaches directly to the tree. Ganoderma whose growth medium is in wood/trees, Ganoderma belongs to